THE IMPORTANCE AND FUNCTIONS OF THE PATTERN IN INTERIOR DESIGN - Berdiyev Doston Abduvoitovich; Mirtolipov Mirvohid Mirzohid o‘g‘li (Web of Journals Publishing, 2025)
The article considers the role and functions of patterns in interior design. It also provides information and recommendations about the types of patterns and their significance.
Keywords: interior, combination, style, rapporta, composition, pattern.